The Urgency of Reformulating the Material Legality Principle in the Criminal Code Based on Godly Justice - Aldi Yudistira (Perantara Law Review, 2024)
Indonesia's independence in 1945 provided an opportunity to reform the law, including criminal law reform. Until now, the Criminal Code still adopts the colonial legacy formal legality principle which tends to be positivistic and does not reflect substantive justice and values that live in society. This study aims to analyze the relevance and urgency of reformulating the principle of material legality in creating divine justice in line with the values of Pancasila. The research uses normative juridical method with analytical descriptive approach, relying on literature study, and analyzed qualitatively. The results show that the principle of material legality in the current national Criminal Code does not reflect divine justice, because the living law is only interpreted as customary law, without accommodating religious law. Reformulation of the principle of material legality is needed based on three urgencies: philosophical, sociological, and juridical. Philosophically, living law must include religious law and customs that still exist in society. Sociologically, religious law in many regions is the main guideline, but has not been accommodated in the Criminal Code. Juridically, limiting living law to customary law creates a legal vacuum that can be addressed by including religious law. This reformulation is a strategic step to build a criminal law system that is based on divine justice, in accordance with the values of Pancasila and the 1945 Constitution, and meets the needs of diverse Indonesian communities.